Somerset County, N.J., militia notebook
Militia notebook (46 pages) recording financial payments.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: New Jersey -- History -- 1775-1865.; Somerset County (N.J.) -- Militia; Somerset County (N.J.) -- History